KRISIS REGENERASI PENGRAJIN TENUN DI DESA TROSO: KRISIS REGENERASI PENGRAJIN TENUN DI DESA TROSO - Saffana Azyu Marnis; Atika Wijaya (UNIB Press, 2024)
Troso weaving is a local Indonesian cultural heritage with high aesthetic and historical value and is an integral part of the social, cultural, and economic life of the people of Troso Village. However, this tradition faces challenges in the form of a crisis of artisan regeneration. The purpose of the study is to explain the factors that cause the low interest of the community in becoming Troso weaving craftsmen and the impact that occurs. The research method used is descriptive research with a qualitative approach. The subject of this research is Troso weaving artisans. The researcher used the rational choice theory by James S. Coleman to analyze the problems in this study. The results of the study show that the factors that cause this regeneration crisis are the emergence of other job alternatives, changes in the mindset of the younger generation, lack of family support, and the need for high skills. The impact of this crisis includes a decrease in the number of skilled workers and the threat of extinction of the Troso weaving tradition. Utilizing the findings in this study, a strategy is needed to create a balance between preserving traditions and meeting the needs of the economy and the development of the times.